Football-specific extension of the IOC consensus statement: methods for recording and reporting of epidemiological data on injury and illness in sport 2020 - Waldén, M.; Mountjoy, M.; McCall, A.; Serner, A.; Massey, A.; Tol, J. L.; Bahr, R.; D'Hooghe, M.; Bittencourt, N.; Villa, F. D.; Dohi, M.; Dupont, G.; et al. (British Journal of Sports Medicine, 2023)
Several sports have published consensus statements on methods and reporting of epidemiological studies concerning injuries and illnesses with football (soccer) producing one of the first guidelines. This football specific consensus statement was published in 2006 and required an update to align with scientific developments in the field. The International Olympic Committee (IOC) recently released a sports-generic consensus statement outlining methods for recording and reporting epidemiological data on injury and illness in sport and encouraged the development of sport-specific extensions.